Comprehensive multi-omics, behavioral and morphological analysis of the hazards of nano-plastics in mice with internal carotid artery occlusion - Lu Wang; Jia-Qi Ma; Li-Jia Song; Xiao-Peng Qu; Yue Zhang; Hai-Ming Fan; Chao Wang; Long-Long Zheng; Guo-Dong Gao; Yan Qu; Liang-Liang Shen; Bei Liu (Ecotoxicology and Environmental Safety)
Accumulation of nanoplastics (NPs) poses a severe threat to the homeostasis of the internal environment in patients with chronic diseases. The effects of NP contamination on health in chronically ill populations must urgently be elucidated. In this study, NPs injected via the tail vein were distributed in the brain and internal organs in a mouse model of chronic internal carotid occlusion. Mice with chronic internal carotid artery occlusion exposed to NPs showed behavioral abnormalities, such as depression and anxiety, thus indicating detrimental effects of NPs on the brain. Subsequently, we used proteomics and metabolomics to analyze the specific mechanisms underlying the damaging effects of NP deposition in the brain. The findings helped explain the differences in the underlying biochemical responses at the microscopic level in mice after NP exposure. The NPs not only accumulated in the brain and caused pathologic damage, but also contributed to accelerating atherosclerosis in the mouse model of internal carotid artery occlusion. This work confirms the risk of NPs in a model of internal carotid artery occlusion and elucidates the mechanism underlying this harm; moreover, it provides theoretical support for developing strategies to decrease microplastic intake in patients with internal carotid artery occlusion.